Negative urgency and the dual pathway model of bulimic symptoms: A longitudinal analysis. (15th October 2018) - Puccio, Francis; Fuller‐Tyszkiewicz, Matthew; Buck, Kimberly; Krug, Isabel
Abstract: Objective: This study extends the dual pathway model (DPM) of bulimic symptoms by considering the bidirectional effects amongst symptoms of depression, dietary restraint, and bulimia. We also assessed the influence of negative urgency, a personality construct associated with bulimic symptoms, on the DPM. Method: Participants were 244 females ( M age  = 23.77 years) from the general community. Variables pertinent to the DPM as well as negative urgency were assessed at baseline, and symptoms of depression, dietary restraint, and bulimia were reassessed at 1‐month follow‐up. Results: Excellent model fit was obtained once modifications were made to the DPM and the extended model that included negative urgency. Cross‐sectional paths replicated the DPM as hypothesized, with the exception that time 1 (T1) body mass index failed to predict T1 body dissatisfaction. Although no bidirectional effects were observed, T1 depression predicted dietary restraint at time 2 (T2). Negative urgency was shown to provide incremental predictive utility of T1 pressure to be thin, T1 body dissatisfaction, and T1 and T2 depression. Conclusion: Findings lend support to the DPM and suggest that depression might be a risk factor for later dietary restraint. The results are also consistent with the notion that negative urgency may be an independent risk factor for symptoms of bulimia. However, short‐term longitudinal effects of these putative risk factors require further evaluation.